2008
DOI: 10.1542/peds.2008-1315l
|View full text |Cite
|
Sign up to set email alerts
|

Selected Complementary Feeding Practices and Their Association With Maternal Education

Abstract: OBJECTIVE. As infants transition from a milk-based diet to one that includes most food groups, the timing of the transition, how infants are fed, and the quality of their diet can have important health implications. Our objective is to describe these factors for US infants.METHODS. We analyzed data from the Infant Feeding Practices Study II. Sample sizes varied for relevant questions from ϳ1600 to ϳ2400. We analyzed the prevalence of 14 feeding practices and their association with the mothers' education and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
4
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 23 publications
5
71
4
3
Order By: Relevance
“…Two studies from Malaysia and Brazil had shown similar picture [10][11] . In USA, two studies showed that 21% of the mothers introduced solid foods before four months and early introduction of solid foods was common among low-income women [12][13] . 34% mothers started complimentary foods before four months of age in Italy, 16% before three months in Germany and 51% before four months in UK [14][15][16] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies from Malaysia and Brazil had shown similar picture [10][11] . In USA, two studies showed that 21% of the mothers introduced solid foods before four months and early introduction of solid foods was common among low-income women [12][13] . 34% mothers started complimentary foods before four months of age in Italy, 16% before three months in Germany and 51% before four months in UK [14][15][16] .…”
Section: Resultsmentioning
confidence: 99%
“…In USA, many mothers fed commercial baby juice to their babies even before 6 months of age, which was peak at nine months 12 . Another study from USA also showed that lowincome mothers fed excessive juices and sugary drinks to their children 13 .…”
Section: Disclosurementioning
confidence: 99%
“…Five groups of potential explanatory variables were identified from the literature (Fein, Labiner-Wolfe, Scanlon, & Grummer-Strwan, 2008;Upul, Sanjeeva, Hiranya, Indika, & Michael, 2012;Khanal et al, 2013;Melkam, Molla, Zelalem, & Azeb, 2013;Brown et al, 2014;Issaka et al, 2015a, b).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…In Norway and the USA, only 21% percent of infants were introduced to solid foods before the age of 4 months. 20,21 WHO and UNICEF already recommend the introduction of nutritionallyadequate and safe, complementary (solid) foods at 6 months of age, together with continued breastfeeding for up to two years of age or beyond. 1 A Netherland study found that maternal high education level was related to a high percentage of starting breastfeeding and duration of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%